A VHF Crystal Oscillator for Satellite Receiver - Olesco, Richard O.
This paper will discuss the design of a crystal oscillator used as a local oscillation (LO) for satellite receivers in the VHF band.
Keywords: Communications engineering; Vhf crystal oscillator